The genius within : discovering the intelligence of every living thing - Vertosick, Frank T. (New York : Harcourt, 2002)
Illustrates the profound intelligence of every living thing, from the smallest virus to the entire ecosystem.
Includes bibliographical references (p. [336]-343) and index.
Booklist.
Choice.
Library Journal.
Adult
Keywords: Adaptation (Biology); Biological control systems; Intellect; Adaptation (Biology); Intellect; Nervous system